At the Limits of Cure. - Venkat, Bharat Jayram. (Critical Global Health: Evidence, Efficacy, Ethnography Series, 2021)
Drawing on historical and ethnographic research on tuberculosis in India, Bharat Jayram Venkat explores what it means to be cured and what it means for a cure to be partial, temporary, or selectively effective.